Micropropagation of Clitoria ternatea L. (Papilionaceae) through callus regeneration and shoot tip multiplication - LAWRENCE, G M NAIR, K PRADIP KUMAR, E V SONIYA, BEENA (Journal of Spices and Aromatic Crops, 1993)
Methods for rapid multiplication of Clitoria tematea through callus regeneration and shoot tip cultures are described. Stem and leaf explants cultured on Gamborg’s basal medium supplemented with 0.01-1 mg 1-1 2, 4-dichlorophenoxy acetic acid in combination with 0.01-2 mgl-1 kinetin or 1-3 mgl-1 benzyl adenine alone formed callus. These calli on transfer to Gamborg’s medium supplemented with 1-2 mgl-1 benzyl adenine and 2-3 mgl-1 indole-3-acetic acid or 3-4 mg 1-1 indole-3-acetic acid alone developed shoot buds and the number of regenerated buds was maximum (8-10) with 2 mgl-1 benzyl adenine and indole-3-acetic acid containing medium. Callus retained the same morphogenic potential even after repeated subculturing .. Multiple shoots were induced from the shoot tips cultured on Gamborg’s medium containing 3-5 mgl-1 benzyl adenine, 1mgl-1 benzyl adenine with 2 mgl-1 gibberellic acid. Shoots, developed from shoot tips, multiplied further by subculturing in the same medium or from callus, were rooted in Gamborg’s medium containing 1-3 mgl-1 I-naphthalene acetic acid. The regenerated plants were transferred initially to vermiculite and later grown to maturity in the green house in garden soil and sand (1:3).